S54 The effects of E-cigarettes on pulmonary inflammation and inflammasome activation. (December 2018) - Bell, RL; O'Kane, C; Shyamsundar, M; Dombrowski, Y
Abstract : Introduction and aims: E-cigarettes are marketed as an aid to quit smoking, but nothing is known about their effects on health. Cigarette smoke is known to activate a group of intracellular complexes called inflammasomes, releasing pro-inflammatory IL-18 and IL-1beta via caspase-1 cleavage. Studies have shown chemicals in vaporised E-liquids also found in cigarette smoke. E-liquids have been shown to increase cellular ROS generation and inflammatory cytokine release suggesting that E-cigarette usage might activate inflammasomes. We aim to assess the effect of E-liquid on human pulmonary cells and hypothesise that E-cigarette use induces pulmonary inflammation and inflammasome activation. Methods: To establish models, alveolar epithelial-like cells (A549) and monocyte derived macrophages (THP-1) were used. Additionally, primary human macrophages where isolated from blood. Cells were stimulated either with E-liquids or E-Liquid that had been vaporised and dissolved in cell culture medium. E-liquid was dripped in at 0.3% V/V and vapour was dissolved at a concentration equal to a previously used model for cigarette smoke extract. Supernatants where collected at 2, 4, 24, 48 and 72 hours. Cells where lysed and fixed. Markers of inflammasome activation (IL-1beta, IL-18, caspase-1) and general markers of inflammatory response (IL-8, IL-6) were analysed by ELISA and Western blot. Inflammasome activation was assessed by Apoptosis associated Speck like protein (ASC), an adaptor protein in inflammasome formation, in ASC-reporter cells. Cytotoxicity was determined by lactate dehydrogenase (LDH) release. Results: E-liquid containing nicotine induced 60% (SD=8.387) cell death in THP-1 macrophages compared to negative control at 35% (SD=0.723) (n=3, p<0.05). Vaporised Cinnamon flavoured E-liquid induced 59% (SD=30.500) cell death in epithelial cells compared to negative controls at 15% (SD=2.153) and 91% (SD=10.710) cell death in THP-1 macrophages compared to negative controls at 44% (SD=2.730) (n=3, p<0.05). An average increase of 25 inflammasomes formed per field of view, as measured by ASC speck formation, is seen when THP-1 cells are treated with LPS and vaporised E-liquid for 2 hours compared to LPS alone (n=4). Conclusion: E-cigarettes have the potential to cause pulmonary cytotoxicity and increase immune responses to bacterial and microbial pathogens such as LPS via inflammasome activation.